Dampak Media Sosial Tiktok Terhadap Remaja X di SMA Muhammadiyah Kota Makassar - Nabilah Luthfiyyah; Sam’un Mukramin (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to identify the impact of social media tiktok on youth X at Muhammadiyah High School Makassar City. There are many factors that can influence juvenile delinquency, including family, peer, environmental, and individual factors such as the inability to cope with stress and emotions. It is important to note that not all youth commit delinquency, and some youth may engage in some of these acts without realizing the negative impact. Therefore, it is important for parents and educators to provide good education and positive instruction about good and bad behavior, and help youth develop good social and emotional skills to deal with pressures and problems in life. Juvenile delinquency can be influenced by social media, which is a very popular place for teenagers to communicate, share information, and interact with others. This type of research uses qualitative methods with interview data collection techniques. The informant of this study was one of the X students who used the social media application, Tiktok. The results of this study indicate that the tiktok social media application can have a negative influence on female students if they are not wise in creating content.